Tax Incentives And Trust In Authority: Quasi-Voluntary Tax Compliance Experiments - Matasik, Ade Lisa; Ardiyanti, Wilma Dian; Mutia, Surianti (UNIVERSITAS PAKUAN, 2024)
This study aims to analyze the role of giving tax incentives to voluntary tax compliance and to identify the relationship between trust in authority and voluntary tax compliance. This research is a quasi-experimental study using students who have studied taxation courses. This study used a 2 x 2 factorial design used in designing this study. The first factor is tax incentives which consist of two levels, namely: taxpayers who are aware of tax incentives and taxpayers who are not aware of tax incentives. The second factor is trust in authority which also consists of two levels, namely taxpayers have high trust in authority and taxpayers have low trust in authority. The results of the study show that taxpayers who are aware of tax incentives and have high trust in the tax authorities will produce high voluntary tax compliance. Taxpayers who also have high voluntary tax compliance. The results of the interaction show that taxpayers who are aware of tax incentives and/or have high trust in the tax authorities will show different voluntary tax compliance. The role of tax incentives has a big influence when compared to trust in the tax authorities.